2019
DOI: 10.1002/acn3.50875
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in frontotemporal lobar degeneration with progranulin or C9ORF72 mutations

Abstract: Objective To identify clinicopathological differences between frontotemporal lobar degeneration (FTLD) due to mutations in progranulin (FTLD‐GRN) and chromosome 9 open reading frame 72 (FTLD‐C9ORF72). Methods We performed quantitative neuropathologic comparison of 17 FTLD‐C9ORF72 and 15 FTLD‐GRN with a focus on microglia. For clinical comparisons, only cases with high quality medical documentation and concurring diagnoses by at least two neurologists were included (14 FTLD‐GRN and 13 FTLD‐C9ORF72). Neuropathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
6
20
0
Order By: Relevance
“…Microglial dystrophy has not been compared previously between FTLD and AD, but as dystrophy was similarly severe in all regions, this suggests that there is a common mechanism of excessive microglial senescence. Few studies have examined dystrophy in FTLD, mainly in genetic cases, but these indicate that dystrophy varies regionally and according to potential disease mechanism [53,54], and our results support this. More severe dystrophy was generally observed in white matter than grey matter and this may explain the poor activation of phagocytic and antigen-presenting microglia, and low burden of Iba1-positive microglia, in white matter of most FTLD and AD cases.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Microglial dystrophy has not been compared previously between FTLD and AD, but as dystrophy was similarly severe in all regions, this suggests that there is a common mechanism of excessive microglial senescence. Few studies have examined dystrophy in FTLD, mainly in genetic cases, but these indicate that dystrophy varies regionally and according to potential disease mechanism [53,54], and our results support this. More severe dystrophy was generally observed in white matter than grey matter and this may explain the poor activation of phagocytic and antigen-presenting microglia, and low burden of Iba1-positive microglia, in white matter of most FTLD and AD cases.…”
Section: Discussionsupporting
confidence: 80%
“…This study extends the few previous studies of microglial dystrophy in genetic FTLD, which have focused on FTLD-GRN or FTLD-C9orf72 [42,53,54] and describes dystrophy in FTLD-MAPT for the first time. Dystrophy was consistently extensive, particularly in FW, in all regions in FTLD-GRN cases, where there was punctate, diffuse Iba1 staining consistent with total loss of cell integrity and generalised distribution of microglial debris [16].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additional studies reported enlarged lysosomes in microglia in the motor cortex and spinal cord of C9orf72 ALS patients compared to sporadic ALS (sALS) patients (30). Examination of microglia in postmortem brain tissues from patients with frontotemporal lobar degeneration revealed that microglia dysfunction differed between patients with a C9orf72 repeat expansion and patients with a mutation in progranulin, the latter accounting for 5-25% of familial FTD (31,32). This suggests that the specificity of microglia dysfunction depends on the etiology of the patient population, and further emphasizes the need to better understand how microglia contribute to ALS and FTD.…”
Section: Introductionmentioning
confidence: 99%